PHYSICOEVOLUTION OF THE PHYSICAL AND PHYSICOEVOLUTION OF THE PHYSICAL AND PHYSICO EVOLUTION OF THE PHYSICAL AND PHYSICO EVOLUTION OF THE PHYSICAL AND PHYSICO EVOLUTION OF THE PHYSICAL AND PHYSICOEVOLUTION OF THE PHYSICAL AND PHYSICOEVOLUTION OF THE PHYSICAL AND PHYSICO EVOLUTION OF THE PHYSICAL AND PHYSICO EVOLUTION OF THE PHYSICAL AND PHYSICO EVOLUTION OF THE PHYSICAL AND PHYSICOEVOLUTION OF THE PHYSICAL AND PHYSICOEVOLUTION OF THE PHYSICAL AND PHYSICO EVOLUTION OF THE PHYSICAL AND PHYSICO EVOLUTION OF THE PHYSICAL AND PHYSICO EVOLUTION OF THE PHYSICAL AND PHYSICOEVOLUTION OF THE PHYSICAL AND PHYSICO - - F.1*, Laouaraouar; M.T., Halilatalilat; M., . Oustani 2 (university of eloued جامعة الوادي, 2020)
The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physicoThe purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physicoThe purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physicoThe purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physicoThe purpose of this study is to monitor the evolution some physical and physicoThe purpose of this study is to monitor the evolution some physical and physicoThe purpose of this study is to monitor the evolution some physical and physicoThe purpose of this study is to monitor the evolution some physical and physicoThe purpose of this study is to monitor the evolution some physical and physicoThe purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physico The purpose of this study is to monitor the evolution some physical and physicoThe purpose of this study is to monitor the evolution some physical and physico-chemical chemical chemical chemical chemical chemical chemical chemical parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry parameters of four types compost prepared from the mixture oasis waste and poultry manure in different proportions. During the manure in different proportions. During themanure in different proportions. During themanure in different proportions. During the manure in different proportions. During the manure in different proportions. During the manure in different proportions. During the manure in different proportions. During the manure in different proportions. During the manure in different proportions. During the manure in different proportions. During the manure in different proportions. During the manure in different proportions. During the trial, trial, wh ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises ich lasted 218 days, the temperature rises during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C during the thermophilic phase for all treatments, reaching a maximum threshold of 55°C recorded by the treatment ( poultry manure recorded by the treatment (poultry manure recorded by the treatment ( poultry manure recorded by the treatment (poultry manure recorded by the treatment ( poultry manure recorded by the treatment ( poultry manure recorded by the treatment ( poultry manure recorded by the treatment ( poultry manure recorded by the treatment (poultry manure recorded by the treatment ( poultry manure recorded by the treatment (poultry manure recorded by the treatment (poultry manure recorded by the treatment ( poultry manure recorded by the treatment ( poultry manure recorded by the treatment ( poultry manure recorded by the treatment (poultry manure recorded by the treatment (poultry manure recorded by the treatment (poultry manure PM ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive ) + mixture of residues (wheat straw olive residues) (M residues) (M residues) (Mresidues) (M I)). The p)). The p )). The p )). The p)). The pH, EC, H, EC, H, EC, nit rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all rogen, phosphorus and potassium values increase for all treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are treatments at the end of test. On other hand, MO content and C/N ratio are significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. significantly reduced during the trial, especially for treatments containing poultry manure. The result The resultThe result The result s obtai s obtai ned ned show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show that the four prepared composts meet characteristics of a stable, show
artical
Keywords: Composting, Oasis waste Composting, Oasis waste Composting, Oasis waste Composting, Oasis waste Composting, Oasis waste Composting, Oasis waste s, Temperature, pH, EC, C/N, Arid zones. , Temperature, pH, EC, C/N, Arid zones., Temperature, pH, EC, C/N, Arid zones., Temperature, pH, EC, C/N, Arid zones. , Temperature, pH, EC, C/N, Arid zones., Temperature, pH, EC, C/N, Arid zones. , Temperature, pH, EC, C/N, Arid zones. , Temperature, pH, EC, C/N, Arid zones. , Temperature, pH, EC, C/N, Arid zones., Temperature, pH, EC, C/N, Arid zones. , Temperature, pH, EC, C/N, Arid zones. , Temperature, pH, EC, C/N, Arid zones. , Temperature, pH, EC, C/N, Arid zones. , Temperature, pH, EC, C/N, Arid zones., Temperature, pH, EC, C/N, Arid zones., Temperature, pH, EC, C/N, Arid zones.